The effect of product demand on inequality: Evidence from the US and the UK - Marco Leonardi (Institute for the Study of Labor (IZA), 2010)
This paper examines the relationship between product demand and the pattern of rising skill premia and rising employment of skilled workers in the US and the UK since the 1980s. If more skilled workers demand more skill-intensive goods, then an increase in relative skill supply will also induce a shift in relative skill demand. This channel reduces the need to rely on technology and trade to explain the patterns in the data. This paper shows that in the US more educated and richer workers demand more low skill-intensive services (such as cleaning and personal services) but also more skill-intensive services (such as education and professional services). The parametrization of a simple model suggests that this induced demand shift can explain around 7% of the total relative demand shift in the US between 1984 and 2002. Similar results are provided for the UK.
Keywords: J21; J31; 330; Wage inequality; product demand; income elasticity; Gesamtwirtschaftlicher Konsum; Verbraucherausgaben; Konsumentenverhalten; Qualifikation; Lohnstruktur; Einkommenselastizität; Konsumgut; Dienstleistung; Schätzung; USA; Großbritannien